1998
DOI: 10.1021/ie970791m
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Performance of Plate-Type Monolithic Catalysts for Selective Catalytic Reduction DeNOx Applications

Abstract: An approach to the analysis of the plate-type catalysts for high-dust selective catalytic reduction (SCR) applications is herein presented. Commercial systems were studied in the form of slabs. NO x reduction and SO2 oxidation runs were performed spanning a wide range of operating conditions. The results were analyzed on the basis of a 1D model. The estimates of the intrinsic activity parameters and of the effectiveness factors were found to differ significantly among the catalysts under study. Aspects relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Film transport coefficients have been characterized in detail for monoliths with square, circular, and triangular channels 9,11,12 and for the more complex plate-type monoliths. 13,14 From a rigorous perspective, the film transport coefficients are functions of the distance from the inlet, as well as the surface reaction rate. However, Tronconi et al 11,12 demonstrated that mass transfer coefficients may be evaluated from the familiar Graetz-Nusselt analysis of heat transfer across developing laminar boundary layers in confined channels, without consideration of the surface chemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Film transport coefficients have been characterized in detail for monoliths with square, circular, and triangular channels 9,11,12 and for the more complex plate-type monoliths. 13,14 From a rigorous perspective, the film transport coefficients are functions of the distance from the inlet, as well as the surface reaction rate. However, Tronconi et al 11,12 demonstrated that mass transfer coefficients may be evaluated from the familiar Graetz-Nusselt analysis of heat transfer across developing laminar boundary layers in confined channels, without consideration of the surface chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The same approach was also demonstrated for plate-type monoliths by using a weighted average of the coefficients for rectangular and triangular channels to represent the irregular flow cross-sections. 14 We will expand the established mechanism for catalytic NO reduction to include Hg 0 oxidation by resolving film transport from lumped surface reactivities for NO and Hg 0 . Note, however, that it has already been established that pore diffusion within commercial SCR catalysts significantly mediates the overall NO reduction rates.…”
Section: Discussionmentioning
confidence: 99%
“…Many models for selective catalytic reduction of NO x can be found in the literature (Buzanowski and Yang 1990;Beeckman and Hegedus 1991;Svachula, Ferlazzo et al 1993;Andersson, Gabrielsson et al 1994;Beretta, Orsenigo et al 1998;Fu and Pereira 1998;Koebel and Elsener 1998;Roduit, Baiker et al 1998;Snyder and Subramaniam 1998;Tronconi, Cavanna et al 1998;Khodayari and Odenbrand 1999;Chae, Choo et al 2000;Fontes, Byrne et al 2003). These models vary in their levels of complexity as each treats the kinetics and mass transfer in different ways.…”
Section: Simple Computer Code To Model No X Conversionmentioning
confidence: 99%
“…(1)]: [1] 2The most effective reaction temperature for this process is known to be in the range of 300-400 8C. [2,3] However, many studies have been performed to develop new low temperature SCR catalysts that can work well around 250 8C or even below. In this case the SCR unit could be placed behind the electric precipitation and desulfurizer in a power plant to efficiently remove NO x over a wider temperature range and for NO x control in diesel engines.…”
mentioning
confidence: 99%
“…DOI: 10.1002/cctc.201300777 A Highly Distributed Cu x Au y -Deposited Nanotube Carbon for Selective Reduction of NO in the Presence of NH 3…”
mentioning
confidence: 99%